THE COMMUNITY PARTICIPATION IN SURVEYING FOR THE GEO - SOCIAL MAPPING: MON COMMUNITY OF BAN SAOKRADONG, BANG PA - IN DISTRICT, PHRA NAKHON SI AYUTTHAYA PROVINCE - Rukngern, Anek; Kosit, Sutee (Journal of MCU Nakhondhat, 2021)
The Objectives of this research article were to study community participation about exploring the geo - social community mapping in Ban Saokradong, Bang Pa - In District, Phra Nakhon Si Ayutthaya Province, It was an action research for geo - social community mapping of the Mon Community which qualitative method. The Participation of Community in surveying for the geo - social mapping by Mon Community of Ban Saokradong, Bang Pa - In District, Phra Nakhon Si Ayutthaya Province, was one part to restore the Mon’s cultures of people in the community in order that these people could help to conserve, succeed, and continue the cultures as well as traditions to people of new generation. Also, this was to encourage the villagers to realize the importance of their own community development by using geo - social community mapping as a tool. This community is an old village of Mon people; most villagers have been settled down here since their ancestors from generations to generations. There were not many houses then compared to now. The number of population keeps increasing as a result of the development. However, the geo - social community mapping may be constantly changing depending on the social relationship of people in the community, the economic growth, or other factors. Therefore, the related agencies should update their data regularly in order for making updated geo - social mapping and to link the tourism mapping of the community to the tourists outside in order to gain more economic benefits for the community.